Gender features of functional condition of backbone of teenagers with scoliotic posture - Sergiy Afanasiev (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to study mobility of backbone, endurance of muscles of a trunk and to define gender features of functional condition of backbone at children of the middle school age with scoliotic posture depending on the direction of the top of arch of curvature of spine. Material & Methods: 40 girls and 40 boys, including 18 girls and 18 boys with the right-side deformation of backbone in the thoracic department, the left-side - 22 girls and 22 boys are examined. Results: features of changes of indicators, depending on sex of children and frontage of the top of arch of curvature of spine column, are revealed when studying the level of flexibility of backbone and endurance of muscles of a trunk at children of the middle school age with scoliotic posture. Conclusions: it is established that the level of decrease in flexibility of backbone is higher at boys, than at girls, whereas indicators of contractile ability and tone of muscles of "muscular corset" are higher at boys.